Technical Assistance Guide: Job Descriptions and Skills Required for Public Service/Transitional Jobs, Defining and Measuring Basic Workplace Skills - (:unkn) unknown (My University, 2010)
This technical assistance guide is designed as a resource for local governments and community agencies developing public service and transitional jobs programs to engage workers on layoff or unable to find employment during the current recessionary period. It draws upon successful work relief projects developed in Milwaukee County in prior decades along with job and skill descriptions developed for programs considered during the 1990s. The emphasis of the technical assistance guide is on identifying steps communities can take to move quickly into job creation, drawing on the considerable federal and state resources already available and in the public domain. The focus is on job creation and development of clear expectations of each worker’s job responsibilities, basic skills required, transferable skills gained on the job, and the potential for non-subsidized employment after the recession. Tested workforce skill data models are presented, which can be easily updated.
Keywords: job skills; transition jobs; job training